2020
DOI: 10.1111/bjso.12375
|View full text |Cite|
|
Sign up to set email alerts
|

‘Society thinks they are cold and/or incompetent, but I do not’: Stereotype content ratings depend on instructions and the social group's location in the stereotype content space

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 39 publications
10
61
0
Order By: Relevance
“…However, many subsequent studies utilizing the SCM and the BIAS map instructed participants to respond from their individual perspective—what they personally think about the target group. Despite recent concerns about this practice ( Bye and Herrebrøden, 2018 ; Kotzur et al, 2019a ) and emerging evidence about the impact of response instruction format on the warmth and competence scales of the SCM ( Popper and Kollárová, 2018 ; Kotzur et al, 2020 ), little is known about whether instructions inviting responses from individual and shared cultural perspectives influence the BIAS map (including the SCM), especially when applied to target groups that elicit different normative and social desirability concerns, as in Slovakia’s intergroup relations context (the Roma—a stigmatized ethnic minority vs. the Hungarians—a non-stigmatized ethnic minority). In order to fill this gap, we seek to provide novel evidence by testing the hypotheses about the impact of response instruction, target group, and their interaction on the BIAS map scores in a factorial between-subject experiment.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, many subsequent studies utilizing the SCM and the BIAS map instructed participants to respond from their individual perspective—what they personally think about the target group. Despite recent concerns about this practice ( Bye and Herrebrøden, 2018 ; Kotzur et al, 2019a ) and emerging evidence about the impact of response instruction format on the warmth and competence scales of the SCM ( Popper and Kollárová, 2018 ; Kotzur et al, 2020 ), little is known about whether instructions inviting responses from individual and shared cultural perspectives influence the BIAS map (including the SCM), especially when applied to target groups that elicit different normative and social desirability concerns, as in Slovakia’s intergroup relations context (the Roma—a stigmatized ethnic minority vs. the Hungarians—a non-stigmatized ethnic minority). In order to fill this gap, we seek to provide novel evidence by testing the hypotheses about the impact of response instruction, target group, and their interaction on the BIAS map scores in a factorial between-subject experiment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the small number of participants make these findings difficult to generalize. Recently, Kotzur et al (2020) observed that German participants gave less positive assessment of multiple groups “but only on already depreciated stereotype content dimensions” when instructed to respond from the societal perspective compared to the individual perspective instruction. Moreover, they have argued that the mean level differences in reported stereotypes between different responses instructions might not under all circumstances reflect the relative position of different target groups within the two-dimensional stereotype content space ( Kotzur et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations